Per- and Poly fluoroalkyl Substances Removal using Ion Exchange Resins: A Review - Jeongwoo Shin; Soobeen Shin; Byungryul An (대한환경공학회지)
Per-and polyfluoroalkyl substances(PFAS) are extensively used in various industries due to their thermal and chemical stability. However, they are associated with significant health risks and bioaccumulation. To mitigate human and environmental exposure to PFAS, regulations on PFAS concentrations in drinking water are increasingly stringent. As a result, significant global attention has been given to PFAS removal from drinking water, highlighting the urgent need for effective water treatment technologies. In April 2024, the United States Environmental Protection Agency(USEPA) tightened the maximum contaminant level(MCL) for certain PFAS to 4 or 10ng/L, which is significantly stricter than previous standards. In contrast, domestic regulations and management remain comparatively lenient. This paper comprehensively reviews of PFAS removal technologies utilizing ion exchange resins. Ion exchange resins have demonstrated superior removal efficiency compared with activated carbon, particularly for short-chain PFAS. Furthermore, polystyrene-based resins exhibit higher removal efficiency than polyacrylic-based resins due to their greater hydrophobicity. This technology has been evaluated as an effective process for removing both short- and long-chain PFAS, as well as alternative compounds. It is particularly promising for addressing the rising prevalence of short-chain PFAS and their alternatives. However, challenges persist, including the management of concentrated PFAS wastewater generated during the regeneration process and the adaptation of this technology to various water systems. This study highlights the potential of the ion exchange process to mitigate PFAS contamination and address the increasing demand for versatile removal strategies.